2021
DOI: 10.3390/ani11113228
|View full text |Cite
|
Sign up to set email alerts
|

How Happy Are Equine Athletes? Stakeholder Perceptions of Equine Welfare Issues Associated with Equestrian Sport

Abstract: The international governing body for equestrian sports, the Fédération Equestre Internationale (FEI), states that the welfare of the horse must be paramount and never subordinated to competitive or commercial influences. However, there is growing unease about welfare issues from both within and outside the sport. The aim of this study was to understand stakeholder perceptions of current welfare issues within equestrian sport, determine whether there is scope for change, and explore attitudes towards welfare as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(44 citation statements)
references
References 47 publications
3
39
0
2
Order By: Relevance
“…The social licence to use horses in competition is increasingly being questioned [ 64 , 65 , 66 , 67 , 68 ]. The overall low median RHpE score observed in the current study supports the continuing use of horses in affiliated eventing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The social licence to use horses in competition is increasingly being questioned [ 64 , 65 , 66 , 67 , 68 ]. The overall low median RHpE score observed in the current study supports the continuing use of horses in affiliated eventing.…”
Section: Discussionmentioning
confidence: 99%
“…It has previously been observed that ‘…despite the rigorous training that judges receive, they do not protect horses from poor riding or poor welfare. This could be addressed by providing better training to allow judges to recognise and mark down behavioural signs that are indicative of conflict or underlying pain’ [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…The issues that pose the greatest risk are those that are publicly visible (e.g., injury during competition) or that are brought to the public’s attention by activists, whistleblowers, and journalists, some of whom are involved in the sport [ 27 , 29 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ]. However, it is arguable that these are just the tip of the iceberg, and that many less visible welfare issues—which may, over time, enter mainstream public awareness—have a greater impact on horses’ quality of life [ 100 ]. These include the approximately 23 h/day for which many horses are stabled [ 100 ].…”
Section: What Have the Sports’ Regulatory Bodies Done To Date To Main...mentioning
confidence: 99%
“…However, it is arguable that these are just the tip of the iceberg, and that many less visible welfare issues—which may, over time, enter mainstream public awareness—have a greater impact on horses’ quality of life [ 100 ]. These include the approximately 23 h/day for which many horses are stabled [ 100 ]. In this context, the relative absence, in most jurisdictions, of regulations relating to horses’ ‘down time’ compared with the plethora of regulations relating to their experience during competition is notable.…”
Section: What Have the Sports’ Regulatory Bodies Done To Date To Main...mentioning
confidence: 99%
See 1 more Smart Citation